2017
DOI: 10.1152/jn.00436.2017
|View full text |Cite
|
Sign up to set email alerts
|

Methodological considerations for a chronic neural interface with the cuneate nucleus of macaques

Abstract: While the response properties of neurons in the somatosensory nerves and anterior parietal cortex have been extensively studied, little is known about the encoding of tactile and proprioceptive information in the cuneate nucleus (CN) or external cuneate nucleus (ECN), the first recipients of upper limb somatosensory afferent signals. The major challenge in characterizing neural coding in CN/ECN has been to record from these tiny, difficult-to-access brain stem structures. Most previous investigations of CN res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…Not much is known about the response properties of DCN neurons in primates except that they relay sensory information with high temporal fidelity (384). Recent advances in chronic implants will likely lead to insights about neural coding in the DCN (304, 350). …”
Section: Somatosensory Pathwaysmentioning
confidence: 99%
“…Not much is known about the response properties of DCN neurons in primates except that they relay sensory information with high temporal fidelity (384). Recent advances in chronic implants will likely lead to insights about neural coding in the DCN (304, 350). …”
Section: Somatosensory Pathwaysmentioning
confidence: 99%
“…Interestingly, despite DCN neurons being somatotopically arranged across the coronal plane of the nuclei, evidence from our laboratory suggests that activity hotspots are spatially displaced across the surface of these nuclei when evoked from different stimulus locations (Loutit et al, 2017(Loutit et al, , 2019a. Recently, Suresh et al (2017) also showed that macaque cuneate somatotopic maps are rostrocaudally organized, in addition to the medial-lateral and dorsal-ventral organization (Loutit et al, 2019b). Accordingly, attempts to stimulate cutaneous upper and lower body regions of the DCN, in addition to proprioceptive regions in the external cuneate nuclei, nuclei X, and nuclei Z, will have to target reasonably spatially displaced areas (Loutit et al, 2019b).…”
Section: Dcnc Functional Organizationmentioning
confidence: 83%
“…Congruently, the DCN have received attention as a prospective somatosensory neural prosthetic target. Recently, it was shown that chronically implanted microelectrode arrays in monkeys can collect stable recordings, and variations in electrical DCN stimulation can elicit behavioral responses that demonstrate perceptual discrimination (Richardson et al, 2015(Richardson et al, , 2016Sritharan et al, 2016;Suresh et al, 2017). While these studies establish the DCNc as a potential target, there is a severe lack of fundamental knowledge of the DCNc functional organization and somatosensory signal processing, which needs to be addressed before this region can be pursued as a feasible neural prosthetic target.…”
Section: Introductionmentioning
confidence: 99%
“…Given the potentially important role of descending cortical input on cuneate activity 48 , it is perhaps not surprising if the influence of mechanoreceptors is not what would be expected based on those studies. A second potential confound to test our hypothesis is that the neuroanatomy of the primate cuneate nucleus seems to differ from that of the cat 49 . Therefore, additional neurophysiological studies are needed to better understand the neural pathways involved in the generation of ET and how to target them for new interventions.…”
Section: Relationship With the Neural Mechanisms Of Essential Tremormentioning
confidence: 99%